2007
DOI: 10.1128/mcb.01962-06
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-Dependent Protein Kinase Catalytic Subunit Is Phosphorylated In Vivo on Threonine 3950, a Highly Conserved Amino Acid in the Protein Kinase Domain

Abstract: The protein kinase activity of the DNA-dependent protein kinase (DNA-PK) is required for the repair of DNA double-strand breaks (DSBs) via the process of nonhomologous end joining (NHEJ). However, to date, the only target shown to be functionally relevant for the enzymatic role of DNA-PK in NHEJ is the large catalytic subunit DNA-PKcs itself. In vitro, autophosphorylation of DNA-PKcs induces kinase inactivation and dissociation of DNA-PKcs from the DNA end-binding component Ku70/Ku80. Phosphorylation within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
159
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 42 publications
5
159
0
1
Order By: Relevance
“…One role of DNA-PK autophosphorylation appears to be to control the access of DNA repair factors to DSBs, but also to promote dissociation of DNA-PKcs from the Ku heterodimer (Douglas et al 2007). Since our analysis suggests that at least the S337 NR4A phosphorylation is important for the dissociation of NR4A from the DNAPKcs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One role of DNA-PK autophosphorylation appears to be to control the access of DNA repair factors to DSBs, but also to promote dissociation of DNA-PKcs from the Ku heterodimer (Douglas et al 2007). Since our analysis suggests that at least the S337 NR4A phosphorylation is important for the dissociation of NR4A from the DNAPKcs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the precise function of DNA-PKcs autophosphorylation is still under intense investigation, it appears that it controls access of DNA repair accessory factors to DNA ends (Meek et al 2008). In addition, DNA-PKcs autophosphorylation serves to control disassembly of the DNA-PK complex after DNA repair has been completed (Douglas et al 2007). Importantly, however, relevant DNA-PK substrates other than DNA-PKcs have remained unidentified.…”
mentioning
confidence: 99%
“…In this respect, it has been reported that DNA-PKcs can undergo autophosphorylation (Chan et al, 2002;Douglas et al, 2002Douglas et al, , 2007Chen et al, 2005). To date, it is not clear which is the exact role of this event, although some studies have reported that autophosphorylation of purified DNAPKcs results in disruption of the DNA-PK complex in vitro and loss of kinase activity in vivo (Chan and Lees-Miller, 1996;Merkle et al, 2002;Ding et al, 2003;Block et al, 2004;Douglas et al, 2007). This leaves open the possibility that dissociation of the DNA-PK complex from DNA might be necessary for facilitating subsequent repair steps by allowing the assembly of damage-responsive proteins to the site of DNA damage or activating them.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the phosphorylation sites identified (3)(4)(5)(6), phosphorylation in vivo was clearly detected at the Ser-2056 residue and at the Thr-2609 cluster region (3,7,8). Whereas IR-induced DNA-PKcs phosphorylation at Ser-2056 is clearly mediated by the autophosphorylation of DNA-PKcs (7), IR-induced DNAPKcs phosphorylation at the Thr-2609 cluster is mainly dependent on ataxia telangiectasia mutated (ATM) kinase but not DNA-PKcs itself (8).…”
mentioning
confidence: 99%